1998
DOI: 10.1037/0022-3514.74.4.939
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive interdependence: Commitment and the mental representation of close relationships.

Abstract: On the basis of an interdependence analysis, it is proposed that commitment to a close relationship is associated with cognitive interdependence-a mental state characterized by a pluralistic, collective representation of the self-in-relationship. A cross-sectional survey study and a 2-wave longitudinal study revealed that strong commitment to a romantic relationship is associated with greater spontaneous plural pronoun usage, greater perceived unity of self and partner, and greater reported relationship centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
584
4
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 584 publications
(613 citation statements)
references
References 64 publications
19
584
4
6
Order By: Relevance
“…Consistent with this idea, most methods of measuring commitment subscribe to a multiple component view, with some definitions including satisfaction and intrinsic motivation as a basis of commitment (e.g., Rusbult, 1991), and others tapping into more introjected motives (e.g., Frank & Brandstatter, 2002;Johnson, 1991;Lund, 1985). Still other researchers have proposed an identity-based understanding of commitment (e.g., Lydon, 1996), including couple identity and a sense of "we-ness" in their definitions (e.g., Agnew, Van Lange, Rusbult, & Langston, 1998;Johnson, 1991), or have conceptualized commitment as a vehicle for fulfilling one's identity goals (e.g., Brickman, 1987;Burke & Reitzes, 1991;Gollwitzer & Kirchhof, 1998;Kanter, 1972;Wicklund & Gollwitzer, 1982).…”
Section: Relationship-specific Identification and Relationship Commitmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this idea, most methods of measuring commitment subscribe to a multiple component view, with some definitions including satisfaction and intrinsic motivation as a basis of commitment (e.g., Rusbult, 1991), and others tapping into more introjected motives (e.g., Frank & Brandstatter, 2002;Johnson, 1991;Lund, 1985). Still other researchers have proposed an identity-based understanding of commitment (e.g., Lydon, 1996), including couple identity and a sense of "we-ness" in their definitions (e.g., Agnew, Van Lange, Rusbult, & Langston, 1998;Johnson, 1991), or have conceptualized commitment as a vehicle for fulfilling one's identity goals (e.g., Brickman, 1987;Burke & Reitzes, 1991;Gollwitzer & Kirchhof, 1998;Kanter, 1972;Wicklund & Gollwitzer, 1982).…”
Section: Relationship-specific Identification and Relationship Commitmentioning
confidence: 99%
“…Moreover, other people who read about a relationship that was described using the pronoun we versus she and I rated the relationship as being more close and of higher quality (Fitzsimons & Kay, 2004). Indeed, research has shown that participants who use plural pronouns (we, us, our) to describe their romantic relationship are more likely to be committed to that relationship (Agnew, Van Lange, Rusbult, & Langston, 1998). …”
Section: Relationship Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is the role of cognitive organization in relationship strategies (e.g., Agnew, Van Lange, Rusbult, & Langston, 1998;Andersen & Cole, 1990;Baldwin, 1992;Neff & Karney, 2004). Specifically, Showers and colleagues (Showers & Kevlyn, 1999; suggest that strategies for organizing positive and negative beliefs about relationship partners affect how individuals think about partners' negative characteristics and behaviors and predict overall attitudes toward partners and relationship outcomes.…”
mentioning
confidence: 99%
“…For example, partners may distance themselves emotionally or physically (Vangelisti & Young, 2000) or employ cognitively oriented strategies, such as focusing on positive characteristics and ignoring negative ones (Holmes & Boon, 1990;Johnson & Rusbult, 1989). They may even transform negative behaviors into positive ones (e.g., reinterpreting criticism as dedication to detail; Murray & Holmes, 1993).Of particular interest is the role of cognitive organization in relationship strategies (e.g., Agnew, Van Lange, Rusbult, & Langston, 1998;Andersen & Cole, 1990;Baldwin, 1992;Neff & Karney, 2004). Specifically, Showers and colleagues (Showers & Kevlyn, 1999; suggest that strategies for organizing positive and negative beliefs about relationship partners affect how individuals think about partners' negative characteristics and behaviors and predict overall attitudes toward partners and relationship outcomes.…”
mentioning
confidence: 99%